Interpretaciones poéticas de los Salmos Bíblicos en la literatura rusa. Condiciones del surgimiento y el nacimiento de la tradición - химич, Галин (Eslavística Complutense, 2005)
The article is devoted ca the analysis of poetical interpretation of biblical psalms - the original tradition of the Russian literature. From XVII to XX centuries basing of the material of biblical text not only the problems of art forms were solved as it was pointed formerly, but interpretation of idea, the choice and proper treatment presentation, which allow form an opinion about a poet’s outlook frequently. A position and role of interpretation of psalms by Russian poets in the literary process are determined in the work, the historical - cultural pre-condition of such phenomenon appearance are named.